Integrasi Prinsip Shariah Compliance dan Manajemen Risiko Keuangan Pada Lembaga Keuangan Syariah di Indonesia - Fadilah, Nurul; Muhammad Firdaus; M. Yakub (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2025)
The background of this study is the importance of ensuring sharia compliance and effective risk management for the sustainability of LKS. The purpose of the research is: 1) Analyze the principles of Shariah Compliance. 2) Identify and classify the types of risks in LKS. 3) Evaluate the integration of Shariah Compliance principles in risk management practices in LKS. The method used is library research with a descriptive qualitative approach. The results showed that sharia compliance is The principle of Shariah Compliance is important for Sharia Financial Institutions (LKS) to ensure transactions comply with Islamic teachings, such as the prohibition of riba and maysir. The Shariah Supervisory Board (DPS) oversees compliance and recommends products. LKS faces risks such as financing and reputation, requiring ethical risk management. The integration of sharia principles in risk management is important for the halalness of transactions and the sustainability of the Islamic financial system, despite challenges such as limited instruments and lack of trained human resources.